2016
DOI: 10.2196/resprot.5232
|View full text |Cite
|
Sign up to set email alerts
|

Download Your Doctor: Implementation of a Digitally Mediated Personal Physician Presence to Enhance Patient Engagement With a Health-Promoting Internet Application

Abstract: BackgroundBrief interventions delivered in primary health care are effective in reducing excessive drinking; online behavior-changing technique interventions may be helpful. Physicians may actively encourage the use of such interventions by helping patients access selected websites (a process known as “facilitated access”). Although the therapeutic working alliance plays a significant role in the achievement of positive outcomes in face-to-face psychotherapy and its development has been shown to be feasible on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, our participants agree that the holistic needs of patients with chronic illness demand technologies that facilitate a person-based rather than disease-based model of care [ 4 ]. Tools such as online patient diaries that bring the patient experience closer to the HCP [ 7 , 8 ] have the potential to help create the conditions for office visits to incorporate the relational ethics of person-centered care into practice by creating the space for a more effective meaningful exchange of information and negotiation and support of behavior change between patients and HCPs. Some of the frustrations with systems, such as electronic medical records that were not integrated across institutional boundaries, or worries about being inundated with requests if electronic communications were opened up to patients suggest an element of moral distress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, our participants agree that the holistic needs of patients with chronic illness demand technologies that facilitate a person-based rather than disease-based model of care [ 4 ]. Tools such as online patient diaries that bring the patient experience closer to the HCP [ 7 , 8 ] have the potential to help create the conditions for office visits to incorporate the relational ethics of person-centered care into practice by creating the space for a more effective meaningful exchange of information and negotiation and support of behavior change between patients and HCPs. Some of the frustrations with systems, such as electronic medical records that were not integrated across institutional boundaries, or worries about being inundated with requests if electronic communications were opened up to patients suggest an element of moral distress.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of patient-physician communication through a Web-based eHealth portal, patients had the opportunity to create and share narratives outside of the allotted time of their consultations, and these narratives helped physicians develop a better understanding of their patients’ situations [ 7 ]. In a study on the use of a digitally mediated personal physician presence online, it was found that both patients and HCPs welcomed using the platform and benefited from Web-based interaction [ 8 ]. Lygidakis et al identified that HCPs’ perceived barriers to use were usually dispelled upon becoming familiar with the tools and suggest that training is key to addressing this issue [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These were available at four key points in the programme, and included options to customise written text, add photographs and insert audio/video recorded messages. 18 An example of a screenshot of tailored feedback with GP personalisation is shown in figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In the vast scientific literature on telemedicine systems, we have found only a few reports of systems that use data and information coming directly from patients [ 22 - 27 ], although several systems, as for example Philips’ eCareCompanion and eCareCoordinator [ 28 ], are now moving on to collecting this information through tablets or smartphones [ 29 , 30 ]. Surely researchers are exploring the implications of how and when these subjective data are collected, their utility for effective monitoring, and, more relevant from our point of view, whether there is a quality control process for this subjective information and how it works, but results have not reached the publication stage.…”
Section: Introductionmentioning
confidence: 99%